Non-equilibrium dynamics of a double-well Bose–Einstein condensate-dual reservoir system - Rajagopal, Kalai K.; Gafurjan, Ibragimov (Springer, 2021)
We have studied the dynamics of a two-site Bose–Einstein condensate subject to tunnelling coupling (which makes the system a bosonic Josephson junction), having on-site inter-particle interaction (making the system a small Bose–Hubbard model) and in contact with two separate heat baths, which makes the system lossy and potentially drives it into a non-equilibrium state with some heat current. The dynamical calculation of the system is done within the standard quantum generalized Langevin setting, and the heat baths are assumed to have non-zero memory time (Ornstein–Uhlenbeck process). We numerically calculated the time evolution of the population imbalance, coherence and entanglement of the system. We have shown inter-particle interaction, noise and dissipation induced by BEC atoms-reservoir interaction that are crucial in affecting the dynamics of the mentioned physical parameters. The study also indicates that quantumness (non-classicality) of the system is characterized by the interplay between dissipation and inter-particle interaction.